G Protein-Coupled Estrogen Receptor Regulates Actin Cytoskeleton Dynamics to Impair Cell Polarization - Lachowski, Dariusz; Cortes, Ernesto; Matellan, Carlos; Rice, Alistair; Lee, David A.; Thorpe, Stephen D.; del Río Hernández, Armando E. (Frontiers in Cell and Developmental Biology, 2020)
Mechanical forces regulate cell functions through multiple pathways. G protein-coupled estrogen receptor (GPER) is a seven transmembrane receptor that is ubiquitously expressed across tissues and mediates the acute cellular response to estrogens. Here, we demonstrate an unidentified role of GPER as a cellular mechanoregulator. GPER signaling controls the assembly of stress fibers, the dynamics of the associated focal adhesions, and cell polarization via RhoA. GPER activation inhibits F-actin polymerization, and subsequently triggers a negative feedback that transcriptionally suppresses the expression of monomeric G-actin. Given the broad expression of GPER and the range of cytoskeletal changes modulated by this receptor, our findings position GPER as a key player in mechanotransduction.